Relationship between cultural heritage tourism and sustainability: case of Konya, Turkey - Ter, Ümmügülsüm (Związek pomiędzy turystyką kulturalną a stabilnością rozwoju: przypadek miasta Konya, Turcja, 2011)
Sustainability of historical and cultural resources plays nowadays an important role in creating urban development strategies. Turkey has been inhabited by several civilizations which generated a remarkable historical and cultural richness throughout the history. This study, within the scope of sustainable urban development and dynamics, aims at evaluating the cultural heritage potential of Konya, one of the richest settlements in Turkey in terms of historical and cultural resources. As it is noticed Konya lacks an effective and productive use and conservation of its cultural heritage values. The research concludes with some strategies towards the efficient using of the cultural tourism potentials for a sustainable development of the city
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2011, Nr 195, s. 160-170
Keywords: cultural heritage tourism; development of cities; case of Konya